2015
DOI: 10.1159/000369501
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Role of the Health Care Professional in Controlling the Tobacco Epidemic: Individual, Organizational and Institutional Responsibilities

Abstract: Despite a historical inclination to view tobacco use as a defect in character or reason, advances in the neurobiological understanding of human behavior and the associated disturbances in behavior patterns produced by exposure to nicotine lead to a conceptualization of tobacco dependence as a chronic disease of the brain. Far from being ineffective, the health care practitioner is in a supremely enabled position to effect change, given the enormous access health care has to dependent patients and the establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…The magnitude of impact might be expected to be quite high after providers fully integrate tobacco dependence into their personal, organizational, and institutional roles, but system pressures are likely to produce suboptimal change unless significant barriers to engagement have been removed. 27,28 Clarity regarding coding and documentation requirements relevant to the problem are a necessary prerequisite to full adoption. Several key points are important to recognize-primary among them is the distinction between counseling and E/M services.…”
Section: Resultsmentioning
confidence: 99%
“…The magnitude of impact might be expected to be quite high after providers fully integrate tobacco dependence into their personal, organizational, and institutional roles, but system pressures are likely to produce suboptimal change unless significant barriers to engagement have been removed. 27,28 Clarity regarding coding and documentation requirements relevant to the problem are a necessary prerequisite to full adoption. Several key points are important to recognize-primary among them is the distinction between counseling and E/M services.…”
Section: Resultsmentioning
confidence: 99%
“…(Park et al, 2001; Vogt, Hall, & Marteau, 2005) Others have suggested that the institutional responsibility to treat tobacco dependence has not yet been firmly established within the culture of medicine. (Fiore & Baker, 1995; Leone & Evers-Casey, 2015) In addition, several cognitive biases have recently been proposed as possible barriers to effective tobacco dependence treatment by virtue of their influence on perception of treatment success probability. (Leone, Evers-Casey, Graden, & Schnoll, 2015; Leone, Evers-Casey, Graden, Schnoll, & Mallya, 2015) If true, static patterns of physician behavior in the face of well-organized and widely disseminated clinical guidelines may in fact be a function of complex social motivations rather than simple lack of interest or training.…”
mentioning
confidence: 99%